High‐resolution stimulated Raman spectroscopy and analysis of line positions and assignments for the ν2 and ν3 bands of 13C2H4. (18th March 2016) - Alkadrou, A.; Rotger, M.; Bermejo, D.; Doménech, J. L.; Boudon, V.
Abstract : High‐resolution stimulated Raman spectra of 13 C2 H4 in the regions of the ν 2 and ν 3 Raman active modes have been recorded at two temperatures (145 and 296 K) based on the quasi continuous‐wave (cw) stimulated Raman spectrometer at Instituto de Estructura de la Materia IEM‐CSIC in Madrid. A tensorial formalism adapted to X2 Y 4 planar asymmetric tops with D 2 h symmetry (developed in Dijon) and a program suite called D 2 h T D S (now part of the XTDS/SPVIEW spectroscopic software) were proposed to analyze and calculate the high‐resolution spectra. A total of 103 and 51 lines corresponding to ν 2 and ν 3 Raman active modes have been assigned and fitted in wavenumber with a global root mean square deviation of 0.54 × 10 −3 and 0.36 × 10 −3 cm −1, respectively. Due to the fact that the Raman scattering effect is weak, we did not perform in this contribution the line intensities analysis. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Ethylene (or ethene) is a naturally occuring compound in ambient air that affects atmospheric chemistry and global climate. On the Earth, it is a tropospheric pollutant produced by automobiles, biomass fires, plant life and the chemical industry. In the atmosphere, photochemical reactions with molecular oxygen and nitrogen, the hydroxyl radical, and ozone produce formaldehyde, nitrous oxide and formic acid. There is thus a need to investigate its spectrum over a wide spectral range. High resolution stimulated Raman spectra of 13C2H4 in the regions of the v 2 and v 3 Raman active modes have been recorded at two temperatures (145 and 296 K) based on the quasi continuous–wave (cw) stimulated Raman spectrometer at Instituto de Estructura de la Materia IEM–CSIC in Madrid. A tensorial formalism adapted to X2Y4 planar asymmetric tops with D2h symmetry that has been developed in Dijon and a program suite called D2hTDS (now part of the XTDS/SPVIEW spectroscopic software) was proposed to analyze and calculate their high–resolution spectra.